2015
DOI: 10.1016/j.bbadis.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of cardiac sodium channel gene SCN5A expression and function by miR-192-5p

Abstract: The SCN5A gene encodes cardiac sodium channel Nav1.5 and causes lethal ventricular arrhythmias/sudden death and atrial fibrillation (AF) when mutated. MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression, and involved in the pathogenesis of many diseases. However, little is known about the regulation of SCN5A by miRNAs. Here we reveal a novel post-transcriptional regulatory mechanism for expression and function of SCN5A/Nav1.5 via miR-192-5p. Bioinformatic analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Caspase-3 activity in cardiomyocytes was measured by test kits (Sigma, USA), as reported previously [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Caspase-3 activity in cardiomyocytes was measured by test kits (Sigma, USA), as reported previously [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al showed that miR-192-5p was upregulated in the atrial tissue of AF patients, and miR-192-5p regulates the expression of the cardiac sodium channel gene, SCN5A. 32 Furthermore, miR-192 is known to reduce the expression of CAV1, which was found to have an association with AF by a genome-wide association study. 33, 34 The function of the 3 remaining miRNAs (miR-99a-5p, miR-214-3p, and miR-342-5p) has also been reported.…”
Section: Possible Mechanisms Of Novel Mirnas In Relation To Afmentioning
confidence: 99%
“…Jurkat T cells were cultured in 24-well plates at ϳ5 ϫ 10 4 cells/well and transfected with 200 ng of either pMIR-RE-PORT-Myc-3ЈUTR-WT or pMIR-REPORT-Myc-3ЈUTR-MUT and 100 nM miR-451a mimic or negative control NC-miRNA mimics, along with 20 ng of Renilla luciferase vector for normalization as described previously (42). The cell extracts were prepared 48 h after transfection, and the luciferase activity was measured using a Dual-Glo TM luciferase assay system (E2920, Promega).…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%